THE ANALYTICAL STUDY OF CARBONIZED GRAIN REMAINS FROM THE LAKE BALATON REGION (HUNGARY) - GYULAI, F. (Annali di Botanica, 2019)
Methods developed for the measurement of macro as well as trace elements and amino acid contents in food and feed chemistry were applied in the study of carbonized grain finds from Roman Period, Migration Period and Hungarian Late Middle Ages deposit. Even the carbonized state of archaeological grain finds posed no difficulty since this process probably took place slowly and gently. Otherwise not even traces of heat sensitive organic molecules would have survived. The macro elements identified are indicative of large molecule organic compounds. Some of these elements may have already disappeared from the deposits during the primary decomposition of organic molecules and could easily have been bleached by water. Trace elements are significantly more stable. Results of the analyses under discussion here show that the average trace element content of ancient cereals exceeded that of their modern counterparts by some 30%. The mere fact that amino acids could be identified, shows that the carbonized samples were not subjected to rapid burning. It may be assumed therefore that these remains undoubtedly underwent a gentle and slow carbonization process in an anaerobic environment.